P71 Implementation of step-down intermediate care in glasgow city: a qualitative study exploring barriers and enablers. (2nd September 2017) - Levin, KA; Crighton, EM
Abstract : Background: The aim of Step-down Intermediate Care (IC) is to provide a short-term care environment for older people ready for discharge from acute hospital but requiring a period of assessment and/or rehabilitation. There are a number of models of IC in the UK. Glasgow City's model of IC has gone through several iterations and stages of development. This study aims to examine the implementation of IC in Glasgow City, to identify enabling factors and barriers. Methods: The study used multiple qualitative methodologies: document review, semi structured interviews, focus groups and attendance at IC development and care home review meetings. The documentary analysis included reports and meeting minutes. Nine key members of staff were interviewed and three focus groups were run; the first included IC social work staff from Glasgow City's three sectors, the second included rehab staff from two sectors, and the third included care home staff from three IC units. Framework analysis was used to identify common themes. Results: Perceived enablers common to all staffing groups included: buy-in from a range of stakeholders, strong leadership and a risk management system in place, good relationship, trust and communication between agencies, the role of targets and in particular the 72 hour discharge target, training of staff, changing perception of risk and risk aversion among practitioners, the right infrastructure and staffing in place, an accommodation based strategy for patients discharged from IC, the right context of political priorities, funding, and a wider model of care for older people, and ongoing adaptation of the model in discussion with frontline staff. Perceived barriers included: differing perception of IC aims, the use of separate technologies by agencies for recording information, transition of patients from hospital to IC, inappropriate referrals to IC, and variation in health and social care systems between sectors and hospitals. Additionally, perceptions differed by staffing group. While social workers noted a need for continuous education of acute staff, and placement issues on discharge from IC, rehab staff found that care homes often lacked appropriate facilities. Both social work and rehab staff noted the benefits of being attached to one unit, while care home staff described the importance of continuity of acute staff. Conclusion: The proposed benefits of IC were understood and supported anecdotally by staff. The development of IC in Glasgow gives an insight into enablers of and barriers to implementation of the service, highlighting further opportunities for improvements to the model.